The role of Public Councils in local institutional decision-making (The cases of Astana and Almaty cities). - Kogay, Alexandra; Shegenova, Ulpan (Nazarbayev University Graduate School of Public Policy, 2018)
The underlying intention of the establishment of Public Councils is implementation of institutional reforms, which in turn aim at enhancing participation of people in the process of decision-making by the state bodies. This initiative is relatively new for Kazakhstani society and therefore, needs the extended research, which will be the first one done on the examples of Astana and Almaty cities. The aim of this research is to identify the barriers that hinder functioning of the Public Councils. The methodology is based on the primary and secondary data analysis, face-to-face interviews, participatory observation and overview of the legislative acts in force.
Keywords: public councils; institutional decision-making